2018
DOI: 10.1080/10749357.2018.1440508
|View full text |Cite
|
Sign up to set email alerts
|

Predicting shoulder function after constraint-induced movement therapy: a retrospective cohort study

Abstract: Background Several predictors have been associated with upper extremity (UE) recovery after stroke, but characteristics that predict shoulder function after constraint-induced movement therapy (CIMT) have not yet been identified. Objectives To identify predictors associated with satisfactory shoulder function in patients with reduced shoulder function at admission to CIMT. Methods One hundred and seventy five patients were treated using CIMT while in a specialized inpatient hospital. Satisfactory shoulder func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Tests began with two static capture periods (standing), followed by measurements during ten repetitions (trials) of two tasks which were ReachLow (WMFT task 5) and ReachHigh (WMFT task 6). These functional tasks were chosen because they did not require grasp and manipulation (Hansen et al, 2018). Each patient was seated on a 45.7 cm high back-less chair facing a 73.5 cm high table.…”
Section: Test Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests began with two static capture periods (standing), followed by measurements during ten repetitions (trials) of two tasks which were ReachLow (WMFT task 5) and ReachHigh (WMFT task 6). These functional tasks were chosen because they did not require grasp and manipulation (Hansen et al, 2018). Each patient was seated on a 45.7 cm high back-less chair facing a 73.5 cm high table.…”
Section: Test Protocolmentioning
confidence: 99%
“…We recently used selected tasks from the WMFT to assess shoulder function after constraintinduced movement therapy (CIMT) and found that a substantial part of the patients reached a positive outcome (Hansen et al, 2018). However, it is challenging to use clinical function tests to identify and evaluate specific changes in the process of recovery (Alt Murphy et al, 2015) and in particular to differentiate between compensatory and non-compensatory movements (Levin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%